KETERLIBATAN SUAMI YANG AKTIF SELAMA KEHAMILAN - Wisesa, Mutmainah; Azzahra, Fatimah; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Media Penelitian dan Pengembangan Kesehatan, 2025)
One important factor influencing moms' and babies' health is the husband's engagement throughout pregnancy. Numerous studies have demonstrated that spouses' active involvement can enhance mothers' physical and mental well-being and solidify family ties.Cultural conventions that view pregnancy as the responsibility of women and spouses' ignorance of pregnancy health frequently hinder this involvement.Reviewing the role of husbands in helping wives throughout pregnancy and identifying the obstacles they encounter are the goals of the study, and the study's ramifications include the necessity of methods to boost husband participation in pregnancy support, including social interventions, health policies, and education.It is anticipated that this will strengthen family ties and enhance the health of mothers and babies.There are inclusion and exclusion criteria, 16 references from 2019–2024, and a narrative review design for the literature study that supports the idea that having a husband during pregnancy benefits both the mother and the fetus.The analysis is presented narratively using data collection methods from the PubMed and Google Scholar databases.The husband's engagement in the pregnancy and the variables influencing it are the primary subjects of discussion.The findings demonstrated that spouses who were physically and emotionally involved throughout pregnancy improved the health of both the mother and the unborn child and improved family ties.Obstacles include societal expectations and husbands' ignorance of pregnancy health issues continue to be problems. This study highlights the value of social interventions and health education for husbands to promote their involvement during pregnancy. Improved maternal and child well-being outcomes are anticipated with increased involvement.